Forgiveness as a predictor of mental health in citizens living in the military conflict zone (2019-2020) - Kravchuk, Svetlana; Khalanskyi, Viacheslav (Journal of Education Culture and Society, 2022)
Aim. Empirical research focused on the study of forgiveness as a predictor of mental health in citizens living in the east of Ukraine in a situation of military conflict. Methods. The participants were 302 Ukrainian citizens (152 women; 150 men): 145 citizens living in eastern Ukraine (74 women; 71 men), aged 18 to 50 years and 157 citizens living in the centre of Ukraine (78 women; 79 men), aged 18 to 50 years. The main research methods were as follows: Mental Health Inventory-5 (MHI-5); Mental Health Outcome (BSI-12); Trait Forgivingness (dispositional) Scale; A Short-Version of Forbearance Scale (FS-8); Forgiveness Measures Decision to Forgive Scale (DTFS); Emotional Forgiveness Scale (EFS); The Adult Hope Scale; Flourish and Secure Flourish Scales. Results. The phenomenon of forgiveness is examined in the article. A more pronounced degree of depression and anxiety was found in citizens living in eastern Ukraine compared to citizens living in the centre of Ukraine. A more pronounced degree of mental health, happiness, and life satisfaction has been observed in citizens living in the centre of Ukraine compared to citizens living in eastern Ukraine. Conclusion. Hope, happiness, life satisfaction, and a tendency to forgiveness are factors of mental health. Tendency to forgiveness is positively correlated with decisional forgiveness, hope, emotional forgiveness, tolerance, and acceptance of others, mental health, happiness, and life satisfaction, as well as tolerance for the mistakes of others.